Great apes can defer exchange: a replication with different results suggesting future oriented behavior - Osvath, Mathias; Persson, Tomas (Frontiers in Psychology, 2013)
The topic of cognitive foresight in non-human animals has received considerable attention in the last decade. The main questions concern whether the animals can prepare for upcoming situations which are, to various degrees, contextually or sensorially detached from the situation in which the preparations are made. Studies on great apes have focused on tool-related tasks, e.g. the ability to select a tool which is functional only in the future. Dufour and Sterck (2008), however, investigated whether chimpanzees were also able to prepare for a future exchange with a human: an object exchanged for a food item. The study included extensive training on the exchangeable item, which is traditionally not compatible with methods for studying planning abilities, as associative learning cannot be precluded. Nevertheless, despite this training, the chimpanzees could not solve the deferred exchange task. Given that great apes can plan for tool use, these results are puzzling. In addition, claims that great ape foresight is highly limited has been based on this study (Suddendorf and Corballis, 2010). Here we partly replicated Dufour and Sterck’s study to discern whether temporally deferred and spatially displaced exchange tasks are beyond the capabilities of great apes. In addition to chimpanzees we tested orangutans. One condition followed the one used by Dufour and Sterck, in which the exchange items, functional only in the future, are placed at a location that freely allows for selections by the subjects. In order to test the possibility that the choice set-up could explain the negative results in Dufour and Sterck’s study, our second condition followed a method used in the planning study by Osvath and Osvath (2008), where the subjects make a forced one-item-choice from a tray. We found that it is within the capabilities of chimpanzees and orangutans to perform deferred exchange in both conditions.